The water footprint of second-generation bioenergy: A comparison of biomass feedstocks and conversion techniques. (1st April 2017) - Mathioudakis, V.; Gerbens-Leenes, P.W.; Van der Meer, T.H.; Hoekstra, A.Y.
Abstract: Bioenergy is the most widely used type of renewable energy. A drawback of crops applied for bioenergy is that they compete with food and use the same natural resources like water. From a natural resources perspective, it would be more efficient to apply the large potential of available crop residues. In this paper, we calculate the water footprint (WF) of ten crop residue types and a few other second-generation bioenergy feedstocks (miscanthus, eucalyptus and pine). Further we estimate the WF of energy carriers produced through different conversion techniques (heat or electricity from combustion and gasification, bioethanol from fermentation and oil from pyrolysis), using the global WF standard. The WFs of crop residues, miscanthus and wood show a large variation. Crop residues have a smaller WF than miscanthus and wood. Given a certain feedstock, the WF of pyrolysis oil is smaller than the WF of bioethanol from fermentation. The WFs of heat from combustion or gasification are similar. The WF of electricity by combustion ranges from 33 to 324 m 3 /GJ and the WF of electricity by gasification from 21 to 104 m 3 /GJ. This research concludes that it is relatively water-efficient to apply crop residues, and that the production of miscanthus and wood for bioenergy is less favourable. Crop residues can best be converted to oil rather than to ethanol. Electricity from gasification has a smaller WF than electricity form combustion; heat from combustion has a smaller WF than heat from gasification. By showing the water efficiency of different feedstocks and techniques to produce second-generation bioenergy, the study provides a useful basis to wisely choose amongst different alternative forms of second-generation bioenergy. Highlights: Second-generation bio-energy from crop residues has high potential to supply energy. Miscanthus and wood are feedstocks for bioenergy with large water footprints. Crop residues are feedstocks for bio-energy with relatively small water footprints. Water footprint of pyrolysis oil is smaller than bio-ethanol for the same feedstock. Water footprint of sugar crop residue (beet or cane) is smallest of all crop residues.